(untitled) (INNOVATIVE ECONOMY, 2019)
Rossokha V.V., Petrychenko O.A. FORMATION OF CONTRACTUAL RELATIONS IN THE DAIRY INDUSTRY ON THE PRINCIPLES OF SMART CONTRACTS AND BLOCK CHAIN TECHNOLOGY Purpose. Examination of the contract content, significance of contractual relations for economic interactions, outlining of the prospects of using smart contracts based on the block chain technologies and development of a conceptual model for the formation of contractual relations between the participants in the dairy industry. Methodology of research. The monographic method of research was used to determine the essence of the contract, establish its economic and legal content, principles of contracting and outline contractual relations in the institutional theory. An overview of legal regulation of contracting in the dairy industry is based on the methods of analysis and synthesis. Substantiation of the advantages and disadvantages of smart contracts regarding traditional contracts is carried out by methods of analogies and comparisons, and the basic principles of technologies of smart contracts and block chain in a digital format and the possibilities of their use were studied by the structural-and-functional and graphic methods. Findings. It is established that the contract interaction of business entities in a market environment involves risk minimization. The article establishes the reliability of the agreement, which is based on the analysis of uncertainty factors, orientation towards economic, rather than the status content of the contract, effective management of contracting. The relationships between the participants in the dairy industry on the basis of contracting are conditioned by the need to ensure a well-organized socio-economic organization. It is proved that the formal nature of contractual relations causes the necessity to use smart contracts that became possible thanks to the block chain technology, simplify the sale relations, facilitate verification of the execution of agreements, allow to trace the entire chain of supply from the manufacturer to the consumer and to make mutual settlements in real time format. The value of smart contracts for participants in the dairy industry and end consumers of dairy products is substantiated. Originality. A conceptual model of the formation of smart contracts in the dairy industry has been developed on the basis of the use of block chain technology, which guarantees the transparency of the production process and radically changes the current practice of managing the enterprises of the dairy industry. Practical value. Implementation of the research results enables agricultural enterprises to properly inspect suppliers of material resources, to ensure the exchange of physical goods along with the exchange of payments. Processing enterprises will be provided with information to check the origin of raw materials and ingredients from their producers, and consumers will be able to check the origin and quality of the dairy products offered in the trade network. Key words: contract; contracting; contractual relations; participants; smart-contract; technology; block-chain; producer; consumer; transaction.